Colorectal adenocarcinomas diagnosed following a negative faecal immunochemical test show high‐risk pathological features in a colon screening programme. Issue 5 (8th December 2020) - Steel, Michael J.; Bukhari, Hussam; Gentile, Laura; Telford, Jennifer; Schaeffer, David F.
Abstract : Aims: The faecal immunochemical test (FIT) is used every 2 years to screen average‐risk British Columbians aged 50–74 years, with follow‐up colonoscopy for positive results. Non‐screen‐detected colorectal adenocarcinomas are defined as those detected within 25 months following a negative FIT. We aimed to more clearly characterise these malignancies. Methods and results: A medical chart and focused pathology review of colorectal malignancies from 926 individuals who completed FIT in the British Columbia Colon Screening Program in 2014, and whose pathology reports were available for review, was conducted. This cohort was divided into two groups: individuals with colorectal adenocarcinomas diagnosed following a positive FIT (screen‐detected) and individuals with colorectal adenocarcinoma diagnosed within 25 months of a negative FIT (FIT‐interval cancers). Rates of clinically relevant pathological parameters, as outlined in the American Joint Committee on Cancer (AJCC), 8th edition, were compared between the screen‐detected and FIT‐interval cancer groups. A total of 876 screen‐detected and 50 FIT‐interval cancers were identified. FIT‐interval cancers exhibited higher rates of high‐grade differentiation (including poorly differentiated and undifferentiated cases; P  < 0.01) and aggressive histotype (signet ring cell and mucinous carcinomas; P  < 0.01) than did screen‐detected cancers after Bonferroni correction. Colorectal adenocarcinoma diagnosed after a negative FIT may therefore be associated with worse prognostic determinants than screen‐detected cancers. Conclusion: FIT‐interval cancers are associated with high‐risk pathological features; the possibility that more aggressive, fast‐growing lesions which arise in the interval after truly negative FITs cannot be ruled out. Further study of a larger cohort of FIT‐interval cancers controlling for interaction among the different pathologic parameters will be undertaken.